2017
DOI: 10.1177/0300060517709613
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of variation in coagulation among children with Mycoplasma pneumoniae pneumonia: a case–control study

Abstract: ObjectiveAcute organ embolism in children with Mycoplasma pneumoniae pneumonia (MPP) has been reported, but changes in coagulation are unclear. This study aimed to investigate changes in coagulation in children with MPP.MethodsA total of 185 children with MMP (cases) and 117 healthy children (controls) were recruited. We measured prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time (TT), and plasma fibrinogen (FIB) and D-dimer levels.ResultsPlasma FIB (3.39 ± 0.96 g/L vs 2.93 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…Subsequent thromboembolism may lead to cerebral artery occlusion, which was observed in approximately half of the patients in the present review, sometimes in more than one territory. Of note, elevated levels of fibrin, D-dimer or fibrinogen were reported in 8 patients, which is consistent with a recent study showing a change in blood coagulation parameters, including plasma D-dimer and fibrinogen levels, in children with recent MP pneumonia infection (55).…”
Section: Discussionsupporting
confidence: 91%
“…Subsequent thromboembolism may lead to cerebral artery occlusion, which was observed in approximately half of the patients in the present review, sometimes in more than one territory. Of note, elevated levels of fibrin, D-dimer or fibrinogen were reported in 8 patients, which is consistent with a recent study showing a change in blood coagulation parameters, including plasma D-dimer and fibrinogen levels, in children with recent MP pneumonia infection (55).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies [ 20 , 21 ] have reported that levels of D-D in children with MPP were higher than those in healthy children and were also higher in severe cases of MPP compared with mild cases, especially in severe MPP with extrapulmonary complications [ 21 ]. Few studies have reported on D-D levels in RMPP or on the monitoring of D-D levels after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An inverse association was observed between thrombocytosis and the presence of M. pneumoniae (8.1%; P <0.001). The frequency of thrombocytosis has been reported to range from 8% to 58% 56,57. In a study conducted in Serbia, there was no difference in the leukocyte and platelet counts with M. pneumoniae infection 9.…”
Section: Discussionmentioning
confidence: 98%